2017
DOI: 10.21037/jss.2017.06.16
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical and radiological results of unilateral posterior pedicle instrumentation through a Wiltse approach with lateral lumbar interbody fusion

Abstract: Background: To assess the clinical outcomes of 44 patients who underwent single-level lateral lumbar interbody fusion (LLIF) with unilateral pedicle screw instrumentation through a paramedian Wiltse approach.Methods: Demographic, comorbidity, clinical assessment, peri-operative, and complication data were assessed. Visual analog scale (VAS), Oswestry disability index (ODI), and short form-12 (SF-12) were used to assess clinical outcomes. Post-operative plain radiographs were assessed for subsidence, cage migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…According to previous studies, both OLIF and LLIF presented lower postoperative VAS and ODI scores compared with preoperative values [8, 9, 38, 39], which is consistent with our results. Furthermore, we have found the postoperative VAS and ODI scores in the OLIF group were better than those in the LLIF group (− 3.25 versus − 2.18; − 3.06 versus − 1.76, respectively), probably due to complications related to the psoas muscle injury in the LLIF group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…According to previous studies, both OLIF and LLIF presented lower postoperative VAS and ODI scores compared with preoperative values [8, 9, 38, 39], which is consistent with our results. Furthermore, we have found the postoperative VAS and ODI scores in the OLIF group were better than those in the LLIF group (− 3.25 versus − 2.18; − 3.06 versus − 1.76, respectively), probably due to complications related to the psoas muscle injury in the LLIF group.…”
Section: Discussionsupporting
confidence: 93%
“…Pooled analysis of nine studies treated with OLIF [3, 8–11, 14, 16, 21, 22] showed that the pooled mean of ODIs varies across studies (I 2 = 94.8%), and the pooled SMD was − 3.06 (95% CI, − 4.03 to − 2.08). Pooled analysis of eighteen studies treated with LLIF [5, 10, 26, 27, 30, 33, 34, 3638, 46, 48, 49, 5154, 57] showed that the pooled mean of ODIs varies across studies (I 2 = 83.9%), and the pooled SMD was − 1.76 (95% CI, − 2.08 to − 1.43) (Fig. 4a and b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if LLIF with unilateral instrumentation can obtain similar results to bilateral instrumentation, this would greatly simplify the procedure and obviate a posture change. Currently, there was a few studies evaluating clinical outcomes about LLIF with unilateral instrumentation 19,20 . However, there have been no reports which directly compared clinical outcomes of LLIF between unilateral and bilateral instrumentation.…”
Section: Clinical and Radiographic Analysis Of Unilateral Versus Bilamentioning
confidence: 99%
“…Numerous studies have reported clinical advantages of the Wiltse approach and MIS‐TLIF in treating degenerative lumbar diseases (blood loss 50–180 ml, hospital stay 2–5 days) 9 , 10 . However, MIS‐TLIF still has the limitations of long fluoroscopy time and a long learning curve and causes tissue trauma to some extent due to the specific tubular compression to the muscle during the operation 5 , 11 .…”
Section: Introductionmentioning
confidence: 99%